PEMBATALAN PUTUSAN BEBAS AKIBAT PENGABAIAN VISUM ET REPERTUM (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 992KPID2020) - Twenthina, Ditria Fridyaswari; Kurniawan, Itok Dwi (Sebelas Maret University, 2022)
This article aims to determine the suitability of the Supreme Court's considerations in canceling the acquittal by Judex Factie in the rape case against Article 253 paragraph (1) of the Criminal Procedure Code. The type of legal research in this article is normative legal research with a case approach. The technique used in collecting legal materials in this research is literature study. This study uses an analytical technique with the nature of deduction using the syllogistic method, which begins with proposing a major premise, followed by proposing a minor premise in the form of legal facts and conclusions will be drawn from these two premises. Based on this research, it was found that the Judex Factie judge at the Oelamasi District Court was proven not to have applied a rule of law or a rule of law was not applied as it should. So that the consideration of the Supreme Court in canceling the acquittal by Judex Factie in the rape case was correct and in accordance with Article 253 paragraph (1) of the Criminal Procedure Code.Keywords: Supreme Court; Consideration; Visum et Repertum